Utilization of Rengasdengklok Historical Site as a Source of Learning Pancasila and Civic Education in Improving Morale Nationalism - Muhammad Rafsan Wiratama; Muhammad Irvan Fadillah Ramadhan; Prayoga Bestari; Dede Iswandi (International Journal Labs, 2023)
This research is motivated by the negative impact of the rapid development of globalization which is the main cause of the decline in the sense of nationalism. The decline in the spirit and attitude of nationalism among the youth is currently getting higher. Youth who should have a sense of love and pride for their country, in fact, have an indifferent attitude that results in their laziness to participate in the flag ceremony, undisciplined, preferring foreign products, and ashamed to wear their own nation's cultural attributes such as the use of batik. This opinion caused various problems among students, namely during the flag ceremony there were still many students who were not disciplined, some did not participate in the flag ceremony at all, did not memorize the Indonesian national anthem, did not memorize Pancasila, did not follow the rules and regulations, and do not respect each other. This research uses a qualitative approach and case study research methods. Data collection techniques carried out in this study were interviews, observations, and documentation studies as well as data analysis techniques by means of data reduction, data presentation, conclusion drawing, and verification as well as data validity. The results of this study indicate that (a) The Rengasdengklok historical site is relevant to be used as a learning resource for Civics because it is full of struggle values that can be used to increase the students' spirit of nationalism. (b) The role of teachers in schools is quite good by coordinating with schools and accommodating students well. (c) The results from the use of historical sites have quite an impact as shown by changes in students' attitudes towards a better direction. (d) while in the process of utilization, there are obstacles and ways to overcome them. External and internal constraints can be resolved by coordination between all elements such as the principal, vice principal of the curriculum section, PPKn teachers, and students.